Forceful Milk Ejection Reflex and Tongue-Tied Neonates' Breastfeeding Behaviour - Marta Muresan; Sorana Muresan (IMR Press, 2024)
Background: Forceful milk ejection reflex in mothers and tongue-tie in infants often cause breastfeeding difficulties. Our purpose was to observe the breastfeeding behavior of tongue-tied neonates, in the presence of forceful milk ejection of their mother versus tongue-tied infants without forceful milk ejection or in the presence of forceful milk ejection in non-tongue-tied infants. Methods: This is an observational, prospective, cohort study. The study was undertaken at the Lactation Institute, in Cluj-Napoca, Romania, between 2012 and 2018. We studied the breastfeeding behavior of neonates attending the Institute. The study includes 80 tongue-tied new-borns of mothers with forceful milk ejection (Group I), compared with the breastfeeding behavior of 40 tongue-tied neonates of mothers with normal let-down (Group II) and 29 neonates without tongue-tie in the presence of forceful let-down (Group III). Descriptive statistics, including numbers and percentages, and SAS software were utilized. Categorical data are presented as counts and percentages and analyzed with chi-square tests, utilizing R and Python software. Statistical significance was set at p-value ≤ 0.001, in some cases at p-value ≤ 0.05 using a chi-square test, sometimes validating the results with Fisher's Exact Test. Proportional Analysis and Post-Hoc Analysis (pairwise Z-tests for proportions) were also carried out to demonstrate the frequency of cases. Results: From Group I, the majority (92.50%) were breastfed effectively in the first week, significantly different from infants in Group II (20%), where frenotomy was more frequent (92.50%) and performed mainly for suckling difficulties (86.48%). The difficult latch had a higher percentage in infants in Group II (92.50%). "Reflux-like syndrome" (93.10%), breast refusal (24.13%), and, choking (93.10%) were more frequent in infants in Group III. Conclusions: The majority of tongue-tied infants, whose mothers had early forceful milk ejection, were able to effectively breastfeed after birth. In this cohort, frenotomy might not be necessary or could be postponed. The presence of tongue-tie only, without fast milk flow, led to suckling difficulties and the need for frenotomy. Reflux-like syndrome, choking, and breast refusal were more present in infants without tongue-tie but with fast milk flow.